2013
DOI: 10.1007/s13317-013-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 associations in inflammatory bowel disease and the enteropathic seronegative spondylarthritis

Abstract: PurposeThis study aims to investigate any associations of the proinflammatory cytokine IL-1 in treated patients with inflammatory bowel disease (IBD) and the enteropathic seronegative spondylarthritis (eSpA).MethodsThirty-four patients with Crohn’s disease (CD), 26 with ulcerative colitis (UC) and 14 patients with SpA participated in the study. Valid clinical indexes, CRP values and the endoscopic and histologic examination were used for the determination of disease activity. IL-1α, IL-1β, IL-1 receptor antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…IL-1β and TNF-α may alter epithelial permeability and facilitate the infiltration of inflammatory cells contributing to tissue damage. Furthermore, they mediate chronic intestinal inflammation by promoting the accumulation of IL-17A-secreting innate lymphoid cells and Th17 CD4 + cells [60][61][62]. Studies have revealed increased frequencies of activated cytotoxic T cells (CD8 + ) in active stages of IBDs close to the epithelial cells that may further exacerbate the inflammatory process through the production of TNF-α and IFN-γ, leading to the increased influx of luminal antigens through epithelial lesions [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β and TNF-α may alter epithelial permeability and facilitate the infiltration of inflammatory cells contributing to tissue damage. Furthermore, they mediate chronic intestinal inflammation by promoting the accumulation of IL-17A-secreting innate lymphoid cells and Th17 CD4 + cells [60][61][62]. Studies have revealed increased frequencies of activated cytotoxic T cells (CD8 + ) in active stages of IBDs close to the epithelial cells that may further exacerbate the inflammatory process through the production of TNF-α and IFN-γ, leading to the increased influx of luminal antigens through epithelial lesions [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1α and IL-1β are mediators of the acute phase of IBD (Vounot-rypidis et al, 2013). In the context of IBD, IL-1α seems to be associated with CD, while IL-1β expression is enhanced in active UC (Vounotrypidis et al, 2013). IL-1β induces the delocalization of ZO-1 and occludin from the TJ, eliminating their effectiveness in maintaining the intestinal barrier.…”
Section: Il-1βmentioning
confidence: 99%
“…Pro-inflammatory cytokines such as TNF-ɑ and IL-1 had a pivotal role to play during acute phase responses in IBD (Vounotrypidis et al, 2013). IL-1 includes IL-1ɑ and IL-1β, which are the key cy- growth factor β are regarded as anti-inflammatory or immunosuppressive cytokines (Neuman, 2004).…”
Section: Interleukinsmentioning
confidence: 99%